PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MELATIH KEMAMPUAN BERPIKIR KRITIS MAHASISWA PGSD UNIPA SURABAYA - Imas Srinana Wardani; Via Yustitia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2017)
The students' critical thinking skills in basic science concept courses need to be trained, so that students can solve the problems faced. Critical thinking is the process of seeking, obtaining, evaluating, analyzing, synthesizing, and conceptualizing information as a guide for developing one's thinking. This research aims to train critical thinking ability of PGSD students in the basic science concept course through the application of inquiry learning model. This research is a qualitative research, Subject in research is student of PGSD class of 2016 PGRI University Adi Buana Surabaya (UNIPA). Methods of data collection is done through observation, tests, and interviews. The result of the research indicate that critical thinking ability of PGSD students of UNIPA Surabaya in subject of basic concept of IPA can be trained by using inquiry model